2022
DOI: 10.3389/fcimb.2022.850509
|View full text |Cite
|
Sign up to set email alerts
|

“Alterations in the Skin Microbiota Are Associated With Symptom Severity in Mycosis Fungoides”

Abstract: Cutaneous T cell lymphoma (CTCL), a non-Hodgkin lymphoma, is thought to arise from mature tissue-resident memory T cells. The most common subtypes include Mycosis Fungoides and Sezary Syndrome. The role of skin microbiota remains unclear in the symptom manifestation of MF. Among 39 patients with MF, we analyzed bacteria colonizing MF lesions and non-lesional skin in the contralateral side and characterized regional changes in the skin microbiota related to MF involvement using the difference in relative abunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Therefore, we hypothesized that MF patients have a more signi cant disturbance of the skin microbiome beyond the mere presence of pathogenic microbes like S. aureus. So far, several reports characterized the MF skin microbiome [23][24][25][26][27] and indicated that (a) a destabilized microbiome and [23,28] (b) the abundance of certain microbial genera like Cutibacteria or Staphylococci [24,25] might be associated with disease severity. However, statistical signi cance was largely not reached, likely because of small sample sizes [24], characterization approaches that lacked resolution at the microbial species level, or because samples were not categorized based on clinical or lesional stages [28].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we hypothesized that MF patients have a more signi cant disturbance of the skin microbiome beyond the mere presence of pathogenic microbes like S. aureus. So far, several reports characterized the MF skin microbiome [23][24][25][26][27] and indicated that (a) a destabilized microbiome and [23,28] (b) the abundance of certain microbial genera like Cutibacteria or Staphylococci [24,25] might be associated with disease severity. However, statistical signi cance was largely not reached, likely because of small sample sizes [24], characterization approaches that lacked resolution at the microbial species level, or because samples were not categorized based on clinical or lesional stages [28].…”
Section: Introductionmentioning
confidence: 99%
“…This work further contributes to a growing body of knowledge that suggests CTCL is a disease associated with global dysbiosis ( 10 16 ). The data herein support our previous findings on the CTCL gut microbiome, namely that patients with more advanced disease demonstrated decreased phylogenic diversity and loss of beneficial commensal taxa in comparison to healthy controls ( 11 ).…”
Section: Discussionmentioning
confidence: 63%
“…Broad-spectrum antibiotic treatment correlates with reduced tumor burden in some patients, and spontaneous CTCL mouse models exhibit mild, indolent disease when housed in germ-free isolators but have rapid disease progression when moved to traditional housing ( 8 , 9 ). Recent work published by our group and others has demonstrated that CTCL patients are globally dysbiotic, with altered skin, gut, and nasal microbiomes ( 10 16 ) and that dysbiosis worsens with disease severity ( 10 12 , 16 , 17 ).…”
Section: Introductionmentioning
confidence: 97%
“…CTCL is characterized by heightened vulnerability to bacterial infections, contributing significantly to disease-related morbidity and mortality. 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 Skin barrier defects induced by malignant T cells are likely ports of entrance for bacterial infection. 28 , 29 , 30 …”
Section: Introductionmentioning
confidence: 99%